2007
DOI: 10.1562/0031-8655(2002)0760197iotrbm2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Tumor Response by Manipulation of Tumor Oxygenation During Photodynamic Therapy¶

Abstract: Photodynamic therapy (PDT) requires molecular oxygen during light irradiation to generate reactive oxygen species. Tumor hypoxia, either preexisting or induced by PDT, can severely hamper the effectiveness of PDT. Lowering the light irradiation dose rate or fractionating a light dose may improve cell kill of PDT‐induced hypoxic cells but will have no effect on preexisting hypoxic cells. In this study hyperoxygenation technique was used during PDT to overcome hypoxia. C3H mice with transplanted mammary carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 61 publications
4
42
0
2
Order By: Relevance
“…In vivo studies have demonstrated an improved efficacy of photodynamic therapies by temporarily increasing O 2 availability [8,19], but in vitro studies have failed to replicate this [7]. Here, we have recapitulated the treatment-enhancing effects of temporary hyperoxia observed in vivo [8,19] by exposing cells to a short period of hyperoxia during treatment, following chronic culture under physioxia ( Figs.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In vivo studies have demonstrated an improved efficacy of photodynamic therapies by temporarily increasing O 2 availability [8,19], but in vitro studies have failed to replicate this [7]. Here, we have recapitulated the treatment-enhancing effects of temporary hyperoxia observed in vivo [8,19] by exposing cells to a short period of hyperoxia during treatment, following chronic culture under physioxia ( Figs.…”
Section: Discussionmentioning
confidence: 79%
“…Here, we have recapitulated the treatment-enhancing effects of temporary hyperoxia observed in vivo [8,19] by exposing cells to a short period of hyperoxia during treatment, following chronic culture under physioxia ( Figs. 1 and 2).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous methods to potentially enhance the mechanism of action of PDT through oxygen manipulation have included the use of light dose fractionation [8], inhalation of carbogen or 100% normobaric oxygen (NBO) [9] or being subjected to hyperbaric oxygen (HBO) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence to date suggests if oxygen levels can be maintained and/or increased prior to, during or after PDT [5] then the efficacy of PDT might be improved. A number of direct and indirect methods have been investigated to improve tissue oxygenation and potentially allow reoxygenation of the tumor including; hyperthermia [11], normobaric oxygen (NBO), oxygen multistep therapy, hyperbaric oxygen (HBO) [12], perfluorocarbons [13], light dose fractionation [14,15] and lowering of the light fluence rate [16].…”
Section: Introductionmentioning
confidence: 99%